ASSESSMENT OF SEXUAL FUNCTION DEPENDING ON METHODS OF APICAL FIXATION FOR PELVIC ORGAN PROLAPSE IN WOMEN - Мирович, Екатерина Евгеньевна (Mother and Baby in Kuzbass, 2024)
Sexual function of 109 patients suffering from pelvic organ prolapse was studied before, after, depending on the methods of its surgical correction. The study was conducted using questionnaires and analysis of data obtained in results got before and 12-24 months after surgical treatment the correlation is based on index of female sexual function (FSFI). It was found that the implementation of organ-preserving technologies in the surgical treatment of genital prolapse in women of reproductive age contributes to the improvement of sexual function in 71 % of cases, which is reflected in a significant increase in the index of sexual function. At the same time, vaginal extirpation of the uterus in patients of reproductive age in 45 % of cases leads to a deterioration in sexual function, which is reflected in a significant decrease in average according to index of sexual function and a twofold decrease in the number of women in a state of sexual comfort.